Modern British Prints 1914-1960. (London : Austin/Desmond Contemporary Books)
Austin, Robert Sargent ; Bawden, Edward ; Copley, John ; Gross, Anthony ; Staite Murray, William ; Nash, Paul ; Nevinson, Christopher R.W. ; Sutherland, Graham ; Gill, Eric ; Jones, David ; etc.
Modern British Prints 1914-1960, Austin/Desmond Contemporary Books, Bloomsbury, London, s.a.
Engels
boek
Keywords: Groot-Brittannië